Bioremediation of Indigosol Blue 04B Batik Effluent by Indigenous Fungal Isolates, Aspergillus spp. - Ratna Stia Dewi; Rina Sri Kasiamdari; Erni Martani; Yekti Asih Purwestri (Journal Omni-Akuatika)
Effluent from the local batik home industry is a serious problem, because the effluent discharge generated is spread in different places. Untreated effluent can cause environmental pollution, such as in groundwater reservoirs,because most is discharged into rivers. The aim of this research was to evaluate the bioremediation potential of indigenous fungi in liquid culture media with Indigosol Blue 04B (IB) batik effluent. The fungi isolates tested were Aspergillus sp. 1, Aspergillus sp. 2 and Aspergillus sp. 3, isolated from dye effluent soil and batik effluent, and compared to white rot fungi (Phanerochaete chrysosporium) as a positive control.   The physiochemical properties of IB batik effluent before and after fungal treatment were investigated. All of these parameters before the fungal treatment were above the recommended standard values based on the Governor regulation of Yogyakarta Special Region No. 7/2010. The level of biochemical oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total suspended solids (TSS), and electrical conductance (EC) was reduce by Aspergillus spp. The highest percentage reduction was achieved by Aspergillus sp. 3, namely 88.34% BOD, 89.11% COD, 75.77% TSS, 85.85% TDS and 71.21% EC, after 3 days of incubation. These results show that the positive control isolate had the lowest value. The study confirms the ability of indigenous fungi isolates in the remediation of IB batik effluent and their potential for future analysis in the treatment of all types of batik effluent.